2020
DOI: 10.1038/s41598-019-57391-x
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs between dispersal and reproduction at an invasion front of cane toads in tropical Australia

Abstract: Individuals at the leading edge of a biological invasion experience novel evolutionary pressures on mating systems, due to low population densities coupled with tradeoffs between reproduction and dispersal. Our dissections of >1,200 field-collected cane toads (Rhinella marina) at a site in tropical Australia reveal rapid changes in morphological and reproductive traits over a three-year period after the invaders first arrived. As predicted, individuals with dispersal-enhancing traits (longer legs, narrower hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Over 60 years since their release in South Florida, cane toad populations have dispersed up to 450 km north (U.S. Geological Survey, 2020). As they have high invasive potential, cane toads have been used as an ectotherm model in ecoimmunology and invasion biology studies covering a wide diversity of topics including: history and geographical dispersal effects on locomotor and reproductive behavior (Brown, Holden, Shine, & Phillips, 2018; Brown, Kelehear, & Shine, 2011; Gruber, Brown, Whiting, & Shine, 2017; Kelehear & Shine, 2020; Kosmala, Christian, Brown, & Shine, 2017), corticosterone (CORT) immune interactions (Brown, Kelehear, Shilton, Phillips, & Shine, 2015; Brown, Phillips, Dubey, Shine, 2015; Brown, Shilton, & Shine, 2011; Brown, Shilton, Phillips, & Shine, 2007; S. T. Gardner, Assis, Smith, Appel, & Mendonça, 2020; S. Gardner et al, 2018; Graham, Kelehear, Brown, & Shine, 2012; Llewellyn et al, 2012), parasitic load (Phillips et al, 2010), genetic and phenotypic modifications (Rollins, Richardson, & Shine, 2015; Stuart, Shine, & Brown, 2019), and interactions of these invasive toads with native fauna (Brown & Shine, 2014; Mayer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Over 60 years since their release in South Florida, cane toad populations have dispersed up to 450 km north (U.S. Geological Survey, 2020). As they have high invasive potential, cane toads have been used as an ectotherm model in ecoimmunology and invasion biology studies covering a wide diversity of topics including: history and geographical dispersal effects on locomotor and reproductive behavior (Brown, Holden, Shine, & Phillips, 2018; Brown, Kelehear, & Shine, 2011; Gruber, Brown, Whiting, & Shine, 2017; Kelehear & Shine, 2020; Kosmala, Christian, Brown, & Shine, 2017), corticosterone (CORT) immune interactions (Brown, Kelehear, Shilton, Phillips, & Shine, 2015; Brown, Phillips, Dubey, Shine, 2015; Brown, Shilton, & Shine, 2011; Brown, Shilton, Phillips, & Shine, 2007; S. T. Gardner, Assis, Smith, Appel, & Mendonça, 2020; S. Gardner et al, 2018; Graham, Kelehear, Brown, & Shine, 2012; Llewellyn et al, 2012), parasitic load (Phillips et al, 2010), genetic and phenotypic modifications (Rollins, Richardson, & Shine, 2015; Stuart, Shine, & Brown, 2019), and interactions of these invasive toads with native fauna (Brown & Shine, 2014; Mayer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dispersal traits increased while female weight and fecundity also increased and age at first reproduction decreased at the edge of the range expansion. Other study systems have shown a trade-off between dispersal and reproduction traits at the edge (Hughes et al 2003;Kelehear & Shine 2020). As Bonte & Dahirel (2017) argue, dispersal can be seen as a life-history trait that evolves independently, and that may be the case here.…”
Section: Discussionmentioning
confidence: 71%
“…Behavioural traits linked to dispersal were expected to have changed more often in invasive species, as dispersal and spread are part of the invasion process, particularly if a non-native species is to thrive. For example, cane toads were found to move faster and follow straighter paths following selection in their new environment, the open Australian landscape (Brown, Phillips, & Shine, 2014; see also Kelehear & Shine, 2020). Environmental conditions in new habitats can be challenging for invasive species, requiring changes in activity, movements or strategies against dehydration.…”
Section: Discussionmentioning
confidence: 99%